SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN BANTUAN DANA KOPERASI DESA MENGGUNAKAN ALGORITMA INTERATIVE DICHOTOMISER 3 (ID3) (STUDI KASUS: DESA GALANG SUKA KECAMATAN GALANG) - Nasrul, Ahmad (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Decision Support System is a system that can help management in making an appropriate decision, which is needed at a management level. This was also the case with the Galang Suka Village Office in determining the assistance of village cooperative funds. So far, the Village Office has not yet determined the acceptance of the Koprasi funding so that it faces obstacles in making the election. Seeing this, researchers are interested in conducting research by applying the Dichotomiser Interative Algorithm 3 (ID3) method to determine the receipt of cooperative funding assistance in this village in a decision support system. It is expected that the results of the research can help the Galang Suka Village